Inverse-micelle synthesis of doxorubicin-loaded alginate/chitosan nanoparticles and in vitro assessment of breast cancer cytotoxicity - Rosch, Justin G. (Colloid Interface Sci Commun, 2018)
Naturally-derived polysaccharides, such as alginate and chitosan, can be assembled to form nanocarriers for the delivery of therapeutic agents. Here we exploit the electrostatic complexation of alginate/chitosan in a water-in-oil (w/o) emulsion process to produce doxorubicin (DOX)-loaded nanoparticles (~80 nm) with exceptional spherical morphology and uniformity. This robust synthetic route utilizes an aqueous phase dispersed in a cyclohexane/dodecylamine organic phase and is capable of encapsulating DOX in the nanoparticle solution. The uptake and efficacy of this novel formulation was evaluated in a murine breast cancer cell line, 4T1, with comparable 72 h IC(50) values of the nanoparticle solution (0.15 μg/mL) and free DOX (0.13 μg/mL). Overall, the favorable performance, physiochemical properties, and their facile production support these nanocarriers as promising platform for the delivery of aqueous soluble drugs.